A mitochondria-targeted far red fluorescent probe for ratiometric imaging of endogenous peroxynitrite. (November 2019) - Shu, Wei; Wu, Yulong; Shen, Tianjiao; Cui, Jie; Kang, Hao; Jing, Jing; Zhang, Xiaoling
Abstract: Peroxynitrite (ONOO − ), one reactive oxygen species, is related to various physiological and pathological activities. However, detailed mechanisms of peroxynitrite in biological systems are not thoroughly understood. Thus, the accurate detection of peroxynitrite with rapid response is essential for revealing its functions. Herein, we present a far red fluorescent probeMito-WQPhOH to ratiometric monitor ONOO − in vitro and living cells.Mito-WQPhOH showed the merits of fast response (<20 s), outstanding selectivity and excellent sensitivity towards ONOO − . Importantly, owing to the good water-solubility, great biocompatibility and excellent mitochondria targeting ofMito-WQPhOH, it was used for ratiometric imaging endogenous ONOO − in living macrophages. Therefore, Mito-WQPhOH could act as a potential tool to reveal mechanisms of ONOO − in biological systems. Graphical abstract: Image 1 Highlights: A far red fluorescent probe for ratiometric imaging of endogenous ONOO − in mitochondria has been developed. The proposed probe shows fast response (<20 s), high selectivity and sensitivity toward ONOO − . The proposed probe exhibits excellent cell permeability and mitochondria-targeting ability in RAW 264.7 cells. The proposed probe could be applied to monitor endogenous peroxynitrite by ratiometric fluorescence imaging.